First Insights Into the Virus and Viroid Communities in Hemp (Cannabis sativa) - Chiginsky, Judith; Langemeier, Kaitlyn; MacWilliams, Jacob; Albrecht, Tessa; Cranshaw, Whitney; Fulladolsa, Ana Cristina; Kapuscinski, Marylee; Stenglein, Mark; Nachappa, Punya (Frontiers in Agronomy, 2021)
Hemp (Cannabis sativa L.) production has increased significantly in recent years; however, the crop has been understudied in the U.S. since its production declined in the late 1950s. Disease identification and management is an increasing challenge for hemp growers across the country. In 2019, beet curly top virus (BCTV) was first reported in hemp in Colorado. Hence, we were motivated to understand the diversity and prevalence of BCTV strains infecting hemp in Colorado. We detected BCTV at high incidence rate (81%) in leaf samples from 12 counties. Two different strains of BCTV, Worland (Wor) and Colorado (CO) were present as a single or mixed infection in hemp leaf samples. Phylogenetic analysis revealed BCTV sequences from hemp formed a distinct group along with BCTV strains CO and Wor. To determine other potential viral and viroid pathogens in hemp, we performed next generation sequencing (NGS). Virome analysis revealed the presence of both virus and viroid sequences that had high nucleotide sequence identity with GenBank accessions for cannabis cryptic virus, cannabis sativa mitovirus, citrus yellow vein associated virus, opuntia-like virus and hop latent viroid. In contrast, tobacco streak virus sequence was highly variable compared to sequences in GenBank suggesting a possible new genotype of this virus. The data presented here has important implications for the epidemiology and management of the various diseases of hemp and will lead to the development of integrated pest management strategies designed to interrupt transmission cycles and facilitate efficient crop production.